The European Union and national macroeconomic policy. - Forder, J (Routledge (Taylor and Francis), 1998)
Considers the way in which the European Union has affected autonomy in macroeconomic policy-making of the member states. It begins with an introduction to economic ideas, and explores current themes surrounding monetary and fiscal policy and European integration, including economic policy co-ordination, objectives in national policy-making and motivations for participating in the European Monetary System. Particular focus is given to the larger member states: United Kingdom, Germany, France, Italy.